The Deep Determinants of the Middle-Income Trap - Linda Glawe; Helmut Wagner (University of Hagen, Center for East Asia Macro-economic Studies (CEAMeS), 2017)
The fundamental, underlying factors of development are often neglected when analyzing the question why countries experience a growth slowdown at the middle-income range. Although these so-called `deep determinants' such as geography and institutions have been found to be decisive for the break out of stagnation and for explaining cross-country income differences by many empirical studies, so far, very little has been done to examine to which extent they are also crucial at more subtle stages of economic development. Our paper aims to contribute to close this gap by focusing on the phenomenon of the middle-income trap (MIT) which has reached increasing attention in the last 15 years. In particular, we are interested in whether the deep determinants have positive or negative impacts on the possibility of a country to experience a prolonged stay within the middle-income range. We focus especially on exogenous variables to avoid endogeneity/reverse causality problems. By using simple statistical hypothesis testing, we show that not all findings of the deep determinants literature can be easily transferred to the MIT phenomenon, especially regarding institutional variables. This may raise the question whether we need new deep determinants of growth for the MIT or at least a modified version taking into account the specific circumstances and characteristics of middle-income countries.
urn:nbn:de:hbz:708-dh9610
Keywords: O10; O11; O43; O50; 330; deep determinants of growth; economic development; economic growth; middle-income trap; geography; institutions; culture